ANALISIS REFLEKSI PADA LOKAKARYA ASESMEN DAN PEMBELAJARAN SEKOLAH PENGGERAK - S, Ayu Purnamasari; Lingga, Leny Julia; Deswari, Dini; Syafriani, Syafriani; Wijoyo, Hadion (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2023)
The purpose of this study is to get a factual explanation of the teacher's understanding in carrying out assessments in the independent curriculum. The method used in this research is a qualitative descriptive survey research approach. Survey research steps are divided into 4 stages, namely preparation, data collection, data analysis, and drawing conclusions. The sample in this study consisted of 23 teachers and principals of class 1 driving schools in Riau province who came from Siak, Indragiri Hilir and Dumai districts. The data in this study were collected using a reflection questionnaire at the assessment and learning workshop. The results of the research show that principals and teachers tend to be able to take advantage of reflection on workshop activities to improve the techniques and methods they use in conducting assessments and learning. Through reflection activities at the mobilizing school workshop, it is hoped that it can contribute to teachers and principals in making appropriate assessments based on the learning process that has been implemented.